Pengaruh Lingkungan Kerja Non Fisik dan Kompensasi Finansial Terhadap Komitmen Organisasi Pada Perusahaan Daerah Air Minum Banyuwangi - Gede Krishnabud, Nyoman; Khusna, Khanifatul; Martha Kristy Naibaho, Herdita (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Company competition is increasingly fierce in the current digital era, companies must be able to face competitive competition by utilizing and managing quality resources optimally. The purpose of this research is to determine the influence of the non-physical work environment and financial compensation on organizational commitment. This research was conducted at the Banyuwangi Regional Drinking Water Company. The research was conducted from September 2020 to December 2022. The research design used was explanatory research. The population used was all employees of the Banyuwangi Regional Drinking Water Company with a sampling technique using saturated samples. The sample in this study was 76 respondents. The data analysis method uses multiple linear regression analysis. Based on the research results, it was concluded that the non-physical work environment and financial compensation had a partially significant positive effect on organizational commitment at the Banyuwangi Regional Drinking Water Company and the non-physical work environment and financial compensation had a simultaneously significant positive effect on organizational commitment at the Banyuwangi Regional Drinking Water Company.